Spinal ischemia: the rehabilitation potential. А clinical case - Svetlana I. Tolstaya; Vladimir V. Belopasov; Evgeny V. Chechukhin (Клиническая практика)
BACKGROUND: Spinal myeloischemia is a rare but severe neurological disease, associated with high incapacitation level and high social-economical costs due to complications developing during the acute phase. The reasons for its development can include vascular malfomations, spinal stroke, extra- and intramedullary tumors, compression of the spinal cord in cases of vertebral fractures, intervertebral disc herniations, stenosis of the spinal canal at the cervical segment, medical manipulations and impaired segmental circulation during the anesthesia, lumbar puncture and surgical interventions. CLINICAL CASE DESCRIPTION: The presented clinical observation provides a description of the iatrogenic complication that has developed in a patient aged 52 years after discectomy and installation of the disc prosthesis due to the development of disco-radicular and spinal conflict, resulting due to the С5/С6 dorsomedial intervertebral hernia, the clinical manifestations of which, besides pain, included weakness in the left upper limb, causally related to the focus of intramedullary ischemia at the unilateral side. At the early post-surgery period, asymmetrical tetraparesis was revealed with the predominance in the distal segments of the left upper limb and with impaired functions of the pelvic organs, caused by the expansion of the ischemia zone in the gray and white matters in the anterior areas of the lower cervical segments of the spinal cord. CONCLUSION: The timely initiation of combined medication therapy and the staged rehabilitation, conducted by the multi-disciplinary team, have provided the restoration of the impaired functions and the quality of life for the patient. The proposed methods can be useful in the treatment of patients with compression-related and non-compression-related vascular myelopathies.